Study of Molecular Docking and Prediction of Toxicity of Morin Analogues as Anti-Cancer Agents and Aromatase Inhibitors - Tooba Abdizadeh (مجله علمی دانشگاه علوم پزشکی کردستان, 2023)
Background and Aim: After lung cancer, breast cancer is the main cause of death from cancer among women. Aromatase is a key enzyme involved in the development of estrogen receptor-positive breast cancer, which catalyzes the final stage of estrogen biosynthesis from the conversion of androstenedione and testosterone, and can be a promising target in the treatment of hormone-dependent breast cancer. In this study, the effects of morin and its analogues on aromatase enzyme were evaluated. Materials and Methods: In this descriptive-analytical study, for bioinformatics assessment, the 3D structure of morin analogues (15 compounds), the standard drug (anastrozole) and aromatase enzyme were obtained from PubChem and PDB databases, respectively. Molecular docking studies in relation to the effects of the compounds on the aromatase enzyme were performed using MOE-2014 software. Then the physicochemical properties and biological activity of the compounds were predicted using Swiss ADME, PASS and Swiss Target Prediction browsers. Results: The findings of the present study showed that morin analogues were non-toxic and favorable in terms of physicochemical properties. Also, all morin analogues were capable of inhibiting the aromatase enzyme. The best docking results belonged to galangin, morin, quercetin and rhamnetin compounds with strong binding energy (-13.90 to -14.79 kcal/mol) compared to anastrozole. The prediction coefficient of biological activities of these compounds was 0.175 to 0.952. Proteases, kinases, oxidoreductases, cytochrome P450 and lyases were the main predicted targets for all proposed compounds in the study. Conclusion: Based on the results of bioinformatics studies, morin analogues, because of their suitable placement in the active site of the aromatase, provide more effective inhibition than the standard chemical drug and can be good candidates for hormone-dependent breast cancer treatment in the in vitro and in vivo studies.